Respon Adaptasi Fisiologis dan Psikologis Pasien Luka Bakar yang Diberikan Kombinasi Alternative Moisture Balance Dressing dan Seft Terapi di RSUP Dr. Sardjito Yogyakarta - Lucia Anik Purwaningsih (IJNP (Indonesian Journal of Nursing Practices), 2015)
Background: Burns are the most severe trauma impact on both physical and psychological. With the limited types of advanced dressings are available in some hospitals, many alternatives were developed based treatment of burns moist (moisture balance dressings alternative) to accelerate wound healing. Non-pharmacological interventions for the treatment of psychological stress with SEFT therapy, the patient›s with SEFT therapy will be relaxed and the mind becomes calm. Relaxation created very infl uential in the healing process. This study aim: To identify the physiological and psychological adaptation response of burn patients were given a combination of alternative SEFT moisture balance dressings and therapies. Methods: Action Research to determine the physiological and psychological adaptation response of burn patients were given a combination of alternative moisture balance and SEFT therapy The sample is the total population that met the inclusion criteria. Result : There were 8 respondents (March - June 2014). Most of the 75% of men, aged between 17-51 years, extensive of wound between 6-55% TBSA, 37.5% stage II, stage III 62.5%.Physiological adaptation response with an wound healing indicator average 42.37 (36-49) showed that physiological adaptation response is adaptive, long time recovering the second degree on average 17.6 days (7-36 days), the average grade III 28 , 8 days (20-40 days). Psychological adaptation response with an acceptance score average 44.5 (40-50) and supported by the results of interviews all indicate an adaptive response to psychological adaptation.Conclusion: Psychological and physiological adaptation response following administration of a combination of alternative moisture balance dressings and therapies SEFT are adaptive.Keywords: Alternative moisture balance dressings, SEFT therapy, physiological adaptation, psychological adaptation